2020
DOI: 10.1021/acs.langmuir.9b03421
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Localized Biodeterioration and Secondary Microplastic Formation by Papiliotrema laurentii Unsaturated Biofilm Cells on Polyurethane Films

Abstract: Painted environmental surfaces are prone to microbiological colonization with potential coating deterioration induced by the microorganisms. Accurate mechanistic models of these interactions require an understanding of the heterogeneity in which the deterioration processes proceed. Here, unsaturated biofilms (i.e., at air/solid interfaces) of the yeast Papiliotrema laurentii were prepared on polyether polyurethane (PEUR) and polyester-polyether polyurethane (PEST-PEUR) coatings and incubated for up to 33 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 55 publications
0
24
0
1
Order By: Relevance
“…The complete hydrolysis of polyurethanes is important because partially degraded polyurethanes will increase the amount of microplastics in the environment. We have observed polyurethane microplastic release in our experiments, 61 and there are several groups attempting to degrade microplastics from different angles. One approach has been to agglomerate the microplastics into larger particulates to reduce their movement in the environment.…”
Section: Polyurethanes (Including Polyester Polyurethanes)mentioning
confidence: 58%
See 1 more Smart Citation
“…The complete hydrolysis of polyurethanes is important because partially degraded polyurethanes will increase the amount of microplastics in the environment. We have observed polyurethane microplastic release in our experiments, 61 and there are several groups attempting to degrade microplastics from different angles. One approach has been to agglomerate the microplastics into larger particulates to reduce their movement in the environment.…”
Section: Polyurethanes (Including Polyester Polyurethanes)mentioning
confidence: 58%
“…[58][59][60] We have recently shown that urethane-rich nanoparticles and microparticles were released during the fungal degradation of a polyester polyether polyurethane coating with analytical data supporting only polyester hydrolysis. 61 It would be inaccurate to describe our results as 'polyurethanase' activity. However, while 'polyurethanase' is not an accurate classification, urethanase is accurate since many of the articles describing urethanease activity focus on the degradation of ethyl carbamate, a carcinogen that can be present in fermented foods and drinks.…”
Section: Hydrolasesmentioning
confidence: 95%
“…Fusarium_oxysporum, an economically important lamentous fungus species of Fusarium, is a large species complex of among plant, animal and human pathogens that attack a diverse array of species in a host-speci c manner [30,31]. Papiliotrema_laurentii is a yeast that commonly inhibits in soil and plant, and has ability to hydrolyze polyester coatings and coat components [32]. Studies also suggested that Papiliotrema_laurentii can accumulate intracellular lipids from inulin hydrolysates [33].…”
Section: Discussionmentioning
confidence: 99%
“…Primary MPs are used in the form of spherules as precursors in the plastic industry, with a wide range of applications such as packaging, o ce equipment, and vehicle construction, or as scrubbing material in personal care products or air-blasting granules and pellets, among other uses (Mani et al 2015). Barlow et al 2020). Microplastics are considered to be more prevalent in the environment than macro or mesoplastics, owning their larger quantities and small sizes (Karbalaei et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Primary MPs are used in the form of spherules as precursors in the plastic industry, with a wide range of applications such as packaging, o ce equipment, and vehicle construction, or as scrubbing material in personal care products or air-blasting granules and pellets, among other uses (Mani et al 2015). Secondary MPs are formed by means of chemical and physical mechanisms such as hydrolytic degradation, photolysis, weathering, ultraviolet radiation or abrasion (Ziajahromi et al 2017;Arhant et al 2019), or via biotic degradation, as biodeterioration (Jang et al 2018; Barlow et al 2020). Microplastics are considered to be more prevalent in the environment than macro or mesoplastics, owning their larger quantities and small sizes (Karbalaei et al 2018).…”
Section: Introductionmentioning
confidence: 99%